Pain symptoms and delays healthcare decision-making in acute myocardial infarction - Ainan, Shafa; Lukitasari, Mifetika; Sari, Efris Kartika; Ahsan, Ahsan; Rohman, Mohammad Saifur; Satrijo, Budi (Universitas Brawijaya, 2026)
Background: Rapid initiation of reperfusion therapy in acute myocardial infarction (AMI) is vital for a favourable prognosis and is significantly affected by the duration from symptom onset to hospital arrival. Previous studies have indicated that cardiac autonomic neuropathy (CAN), prevalent in diabetic patients, may impair pain perception, potentially delaying healthcare-seeking behaviour Objective: This study aimed to compare chest pain characteristics and healthcare-seeking delays between patients with diabetes mellitus (DM) and without DM (non-DM) myocardial infarction. Methods: A cross-sectional study was conducted involving 93 subjects (35 DM and 58 non-DM) diagnosed with either ST-elevation myocardial infarction (STEMI, n=78) or non-ST elevation myocardial infarction (NSTEMI, n=15). Data on symptoms, including pain quality and healthcare-seeking timing within 72 hours of admission, were gathered via a standardized questionnaire. Result: Logistic regression analysis highlighted stabbing pain as a strong predictor (OR = 3.296, p-Value = 0.038), indicating that patients with this symptom are more than three times more likely to delay seeking care. Patients with DM are more frequently reported back-radiating stabbing pain (p<0.05). No significant differences between the groups were observed in pain symptomatology and decision-making delay, although DM patients were more likely to delay seeking care for over two hours. Conclusion: While pain characteristics showed no significant differences between DM and non-DM myocardial infarction patients, DM patients were prone to later healthcare engagement. This delay could be attributed to the misinterpretation of cardiac symptoms as diabetic complications, underscoring the need for targeted patient education. Therefore, strengthened patient education and routine screening for cardiovascular symptoms in individuals with diabetes are essential to support early detection and timely management.